Pengaruh Kesadaran Wajib Pajak, Digitalisasi Pembayaran Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak PBB Di Kecamatan Marelan - Letare Dahlia Simanungkalit; Yusnani Yusnani; Latersia Br Gurusinga (Journal of Innovative and Creativity (Joecy), 2026)
Taxpayer compliance is one of the important factors in increasing regional tax revenue, especially Land and Building Tax (PBB). However, the low level of taxpayer compliance in Marelan District remains a problem that needs serious attention. This study aims to analyze the influence of taxpayer awareness, payment digitalization, and tax sanctions on Land and Building Tax (PBB) taxpayer compliance in Marelan District. This study used a quantitative approach with a survey method through questionnaires distributed to respondents who are Land and Building Tax taxpayers in Marelan District. The sampling technique used was random sampling. The research data were analyzed using multiple linear regression analysis with the assistance of the SPSS program. The results of the study indicate that taxpayer awareness has a positive and significant effect on Land and Building Tax taxpayer compliance. Payment digitalization also has a positive and significant effect on taxpayer compliance because it facilitates the tax payment process to become faster and more efficient. In addition, tax sanctions have a positive and significant effect on Land and Building Tax taxpayer compliance. Simultaneously, taxpayer awareness, payment digitalization, and tax sanctions significantly affect Land and Building Tax taxpayer compliance in Marelan District. This study is expected to provide input for local governments in improving taxpayer compliance through increasing public awareness, optimizing digital payment systems, and implementing firm and effective tax sanctions.